Some behavior features of a female Panthera pardus tulliana during pregnancy and at first parturitions - MAKHAR M ERTUEV; UMAR A SEMENOV (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Ertuev MM, Semenov UA. 2019. Some behavior features of a female Panthera pardus tulliana during pregnancy and at first parturitions. Biodiversitas 20: 1333-1338. The present paper reports the results of the behavioral study of a female Panthera pardus tulliana during pregnancy, and before, during and after parturitions. The study was conducted in the Center of leopard recovery in the Caucasus, located in the mountain zone of the Sochi National Park, Russia. The behavior of Panthera was observed using surveillance cameras. During pregnancy, there is a significant shift in the level and ratio of hormones in the female's body. These internal changes can cause reorganization of the brain divisions which participate in the formation of the behavioral reaction, including female's behavior. We have shown that significant changes occur in the manifestation of individual behavior forms along with the increase of the pregnancy age and the intensification of fetal growth: a decrease in the level of anxiety and fear, and an increase in feed intake. At the end of pregnancy, the frequency of sleep and rest periods increases, but they are short-term. Before parturition, a female experiences painful sensations due to increase motor activity of the fetus, accumulation of toxins, possible hypoxia.